2006
DOI: 10.1038/ni1381
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the canonical Wnt pathway leads to loss of hematopoietic stem cell repopulation and multilineage differentiation block

Abstract: Wnt signaling increases hematopoietic stem cell self-renewal and is activated in both myeloid and lymphoid malignancies, indicating involvement in both normal and malignant hematopoiesis. We report here activated canonical Wnt signaling in the hematopoietic system through conditional expression of a stable form of beta-catenin. This enforced expression led to hematopoietic failure associated with loss of myeloid lineage commitment at the granulocyte-macrophage progenitor stage; blocked erythrocyte differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
386
1
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(411 citation statements)
references
References 54 publications
15
386
1
9
Order By: Relevance
“…Cold Spring Harbor Laboratory Press on May 12, 2018 -Published by genesdev.cshlp.org Downloaded from defects (Kirstetter et al 2006). The deregulation of Wnt signaling as a causative factor in leukemogenesis has become more and more apparent (Klaus and Birchmeier 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Cold Spring Harbor Laboratory Press on May 12, 2018 -Published by genesdev.cshlp.org Downloaded from defects (Kirstetter et al 2006). The deregulation of Wnt signaling as a causative factor in leukemogenesis has become more and more apparent (Klaus and Birchmeier 2008).…”
Section: Discussionmentioning
confidence: 99%
“…73,89 The Wnt and Notch pathway have both been implicated in self-renewal of HSCs 75,89,90 and cooperation between Wnt and Notch in HSCs has recently been suggested by Duncan et al 89 Recent studies have demonstrated that the Wnt/b-catenin pathway must be well controlled to assure normal hematopoiesis, because constitutive activation of Wnt signaling results in multilineage differentiation block and compromised HSC maintenance. 91,92 Taken together, Wnt signaling mediates stimulation of self-renewal and enhanced proliferation of HSCs, as well as reduced differentiation. These are features, which might contribute to leukemogenesis.…”
Section: The Canonical Wnt Pathwaymentioning
confidence: 99%
“…β-Catenin is the key and obligatory mediator of canonical Wnt signaling. Stabilized β-catenin expression expands the pool of HSCs and leads to deficiency in HSCs repopulation capacity [12,13]. Conversely, deletion of β-catenin or Wnt3a leads to defective HSCs long-term maintenance [14,15].…”
Section: Introductionmentioning
confidence: 99%